STEM-21. INVESTIGATING DOT1L AS AN EPIGENETIC VULNERABILITY IN BRAIN TUMOR STEM CELLS. (11th November 2019) - Bozek, Danielle; MacLeod, Graham; Hao, Xiaoguang; Rajakulendran, Nishani; Ahmadi, Moloud; Dirks, Peter; Angers, Stephane; Luchman, Artee; Weiss, Sam
Abstract: Glioblastoma (GBM), the most common and aggressive primary adult brain cancer, is thought to be driven by a small subpopulation of brain tumor stem cells (BTSCs). BTSCs exhibit shared properties with normal stem cells such as self-renewal and multilineage differentiation. These stem cell properties have been proposed to underlie GBM tumorigenicity, treatment evasion and contribute to tumor heterogeneity. To investigate the biology underlying the stem cell properties of GBM, we compared gene essentiality profiles for a panel of BTSCs, fetal neural stem cells and non-GBM cell lines using a CRISPR Cas9 knockout library. Interestingly, from these screens, we identified the histone methyltransferase disrupter of telomeric silencing-1-like (DOT1L) as an essential gene for the growth of BTSCs and fetal neural stem cells but not for non-GBM cell lines. DOT1L is the only known histone methyltransferase responsible for histone 3 lysine 79 methylation, an epigenetic mark associated with active gene transcription. The role of this epigenetic regulator in BTSCs was investigated in depth using EPZ-5676, a clinically relevant small molecule inhibitor. Short-term treatment with EPZ-5676 in BTSCs showed minimal effects on cell viability but led to striking morphological changes, increased neuronal and astrocytic differentiation and a reduction in self-renewal. Longer treatment periods with EPZ-5676 led to a decrease in BTSC proliferation and an increase in apoptosis. Furthermore, BTSCs pretreated with EPZ-5676 led to slowed orthotopic tumor growth and improved overall survival in a SCID mouse model. Overall, these findings suggest DOT1L epigenetically regulates GBM stem cell properties and tumor growth. We are further investigating the mechanisms underlying DOT1L regulation of gene expression in BTSCs with the goal of improving the field's understanding of epigenetics and the therapeutic implications of targeting epigenetic processes in GBM.